Zombie business strategies: The case of Ukraine - Pedro Pardal; Ihor Hurnyak; Aleksandra Kordonska (Entrepreneurial Business and Economics Review (EBER), 2021)
Objective: The objective of the article is to study zombie business strategies in Ukrainian practice and present the influence of traditional and manipulative tools on business activity in conditions of weak institutional environment. Research Design & Methods: We apply linear and logistic regression to estimate the impact of traditional and manipulative tools on the investment possibilities by using data from a sample of small enterprises in Ukraine in 2015-2018. The results of the logistic regression were used to present Nash equilibrium in the payoff matrix to explain the coexistence of traditional and manipulative tools in doing business through the prism of interests of the society as a whole. Findings: Evidence revealed that the Ukrainian market creates a special type of zombie business resulting from ineffective government policy and unfavourable institutional environment. Moreover, in conditions of weak stock market, this practice could be used not only in Ukraine but also expanded to countries with similar problems. The main problem is the fact that – in the case of searching for the desired level of profitability - Nash equilibrium on the Ukrainian market combines manipulative and traditional tools. Implications & Recommendations: Considering the business environment that characterized by unprofitability, the equilibrium between adherents of traditional and manipulative mechanisms is reached on the market where the latter prevail. This situation becomes a serious problem for reforms, as fight against manipulative practices by weak market institutions happens almost outside real business. The problem explains why the government and small business practically coexist by interacting only partially without opposition and counteraction. In the case of searching for the desired level of profitability (if the market is in equilibrium), a reformation or transformation of the system will be accompanied by obvious resistance. Our study informs about the risks and economic effects of zombie firms. We recommend the creation of a favourable institutional environment through effective public policies. Contribution & Value Added: We emphasize the undeniable fact that small business is officially completely unprofitable in Ukraine. The article helps to understand the essence of zombie business. It is one of the first attempts to develop a comprehensive analysis of zombie business by a wide range of manipulative tools of financial statements that apply game theory models.
Keywords: D22; D25; M21; M42; L26; 330; zombie business; strategy; institutions; Nash equilibrium; Ukraine